Kampus Merdeka (Studi Independen Bersertifikat) PT. MariBelajar Indonesia Cerdas: Perancangan Website Pregnancy Assistant - Mayanggi Gapriati; Sekar Nur Wahyuni (Madani: Jurnal Ilmiah Multidisiplin, 2023)
With the rapid advancement of science and technology, significant changes have been brought about in various aspects of life. The increasing changes in working methods have led to the disappearance of many job opportunities while simultaneously giving rise to various new types of jobs. Current university students must be prepared to become skilled, flexible, and resilient learners. PT. MariBelajar, as an Official Partner of Microsoft Indonesia, is consistently committed to providing education about technology so that everyone can adapt and compete in the ever-evolving technological changes of this digital era. PT. MariBelajar Indonesia Cerdas delivers up-to-date materials based on Microsoft's technological developments. This program is designed to assist students in acquiring new knowledge that can be applied in the professional world. The final output of the capstone project involves the development of a pregnancy assistant website. It is hoped that students will be able to develop this website to provide assistance to pregnant mothers during their pregnancy journey.